Decentralization (Localization) and Corruption : New Cross-Country Evidence - Ivanyna, Maksym; Shah, Anwar (2012)
This paper attempts to improve the understanding and measurement of decentralization and its relationship with corruption in a worldwide context. This is done by presenting the conceptual underpinnings of such relationship as well as using superior and more defensible measures of both decentralization in its various dimensions as well as corruption for a sample of 182 countries. It is the first paper that treats various tiers of local governments (below the inter-mediate order of government) as the unit of comparative analysis. In contrast, previous analyses erroneously focused on subnational governments as the unit of analysis which yields invalid cross-country comparisons. By pursuing rigorous econometric analysis, the paper demonstrates that decentralization, when properly measured to mean moving government closer to people by empowering local governments, is shown to have significant negative effect on the incidence of corruption regardless of the choice of the estimation procedures or the measures of corruption used. In terms of various dimensions of decentralized local governance, political decentralization matters even when we control for fiscal decentralization. Further voice (political accountability) is empirically shown to be more important in combating corruption than exit options made available through competition among jurisdictions.